Designing Brand Experience for Local Café: Case Study Surf & Brew Coffee Bar and Eatery at Kedungu Beach Tabanan, Bali - Lukitasari, Rimalinda; I Kadek Kesawa Putra Udayana (INSPIRE : Journal of Culinary, Hospitality, Digital & Creative Arts and Event, 2025)
Kedungu is an emerging tourism area in Bali. It is starting to gain interest from surfers and digital nomad tourists. Starting a café and eatery business in an emerging area can have its own benefits and challenges. There are less competition but the business not only need promote itself but also the destination. Branding is one of important aspect in marketing that can make a business gain competitive differentiation. The research aimed to develop a brand-experience strategy for Surf & Brew Coffee Bar and Eatery at Kedungu Beach. A qualitative descriptive approach was chosen, and the data were collected from interviews, guest comment forms, observation, and literary research. The analysis was done through SWOT analysis and using branding strategy theory and brand-experience framework and the basis of the analysis. The results show that positioning the café as a community hub, capitalizing the richness and exoticness of Indonesian food and coffee, and creating a brand personality that suits beach lifestyle are viable.